2003
DOI: 10.1007/s00787-003-0352-0
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptoms after childhood cancer

Abstract: The posttraumatic stress model has recently been applied to understand the impact of life-threatening illness in adults and in children. From 1991 to 2001, 20 studies have reported posttraumatic stress symptoms and/or posttraumatic stress disorder (PTSD) in childhood cancer survivors and/or their parents. A review of these studies is proposed. Prevalence of posttraumatic stress symptoms and/or PTSD in children and in their parents has been estimated, across studies, between 2 and 20 % in survivors and between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
77
2
19

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 43 publications
4
77
2
19
Order By: Relevance
“…Previous research has revealed that the prevalence of clinically significant levels of PTSD and/or posttraumatic stress symptoms (PTSS) in survivors ranged from 2 to 20%, and young adult survivors tended to show higher levels of posttraumatic stress [27]. Cancer affects not only patients but also entire families.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous research has revealed that the prevalence of clinically significant levels of PTSD and/or posttraumatic stress symptoms (PTSS) in survivors ranged from 2 to 20%, and young adult survivors tended to show higher levels of posttraumatic stress [27]. Cancer affects not only patients but also entire families.…”
Section: Introductionmentioning
confidence: 96%
“…Cancer affects not only patients but also entire families. In cases of childhood cancer, 10-30% of parents of survivors showed symptoms of posttraumatic stress [27]. Several factors may predict PTSS, including the individual's general level of anxiety [9,13], medical factors, posttreatment factors, maternal psychological vulnerability [17], family functioning, and social support [12,21].…”
Section: Introductionmentioning
confidence: 99%
“…PTSD is described in patients having experienced or witnessed an event that involved actual or threatened death or serious injury, or a threat to physical integrity of self or others, and presenting a significant number of symptoms in each of these categories: reexperiencing, avoidance/ numbing, and increased arousal [5]. PTSD has been reported in childhood cancer survivors and/or their parents [6], never in SCD children, and once in a SCD adult [7]. We aimed to determine whether children affected with SCD and/or their parents could present PTSD, and to look for associated medical, psychological or social factors.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: antje.horsch@hmc.ox.ac.uk. DuHamel, Gallelli, Sorgen, & Redd, 1998;Manne, DuHamel, & Redd, 2000;Pelcovitz et al, 1996;Taieb, Moro, Baubet, Revah-Levy, & Flament, 2003), severe burn injuries (Fukumishi, 1998;Rizzone, Stoddard, Murphy, & Kruger, 1994), spinal cord injury (Boyer, Knolls, Kafkalas, Tollen, & Schwartz, 2000), bone marrow transplantation (Heiney, Neuberg, Myers, & Bergman, 1994;Manne et al, 2002), organ transplantation (Young et al, 2003), hematopoietic stem cell transplantation (Manne et al, 2004), traffic-related injuries (de Vries et al, 1999;Winston et al, 2002;Winston, Kassam-Adams, GarciaEspana, Ittenbach, & Cnaan, 2003), meningococcal disease (Shears, Nadel, Gledhill, & Garralda, 2005), and admission to the pediatric intensive care unit (Balluffi et al, 2004). Furthermore, Landolt, Vollrath, Ribi, Gnehm, and Sennhauser (2003) showed that the severity of parental PTSD symptoms was higher in parents of children who had recently been diagnosed with a chronic illness than in parents of children who had recently been involved in an accident.…”
mentioning
confidence: 97%